Optimal sizing of renewable energy systems in a Microgrid considering electricity market interaction and reliability analysis - Hakimi, Seyed Mehdi; Hasankhani, Arezoo; Shafie-khah, Miadreza; Lotfi, Mohamed; Catalao, Joao P.S. (Elsevier, 2022)
This paper addresses the optimal sizing of renewable energy systems (RESs) in a microgrid (MG), where the MG participates in the electricity market. A novel method for reliability analysis is proposed in this study to deal with the high penetration of RESs. In this framework, the MG is considered as a price maker, having a two-direction relation with the electricity market. RESs, including photovoltaic (PV) panels, wind turbines (WTs), and fuel cells, are optimally sized based on the reliability index, and the results are evaluated before and after the MG involvement in the electricity market. The results show a 3.6% decrease in the total cost of the microgrid as a result of the transactions with the electricity market. Furthermore, the efficiency of the proposed approximate reliability method is verified, where the reliability of the MG is evaluated with less computational complexity and acceptable accuracy.
Keywords: Optimal sizing; Reliability; Renewable energy system; electricity market; microgrids; fi=Sähkötekniikka|en=Electrical Engineering|